Flexibility in wage setting under the threat of relocation - Anna Goeddeke; Justus Haucap; Annika Herr; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
Relocation of production to countries with low labour cost have induced increased labour market flexibility, which has been praised as a silver bullet for economic growth and low unemployment. Within a unionised oligopoly framework, in which a multi-national firm has the option to relocate its production to a foreign country, we analyse the welfare implications of both centralised and flexible wage setting regimes. For very low foreign wages, wage flexibility leads to higher welfare than a rigid centralised regime. In contrast, for 'intermediate' wage levels in the foreign country, an industry-wide uniform wage leads to higher social welfare than flexible wages.
Keywords: F23; J51; L13; 330; Union; Centralised Wage; Wage Flexibility; Relocation; Labour Market Flexibility